DESENVOLVIMENTO DE IMUNOSSENSOR ELETROQUÍMICO PARA O MONITORAMENTO DE CÉLULAS CANCEROSAS - Almeida, Sthéfane Valle de (2019)
Cancer is the second leading cause of death globally, and was responsible for an estimated 10 million deaths in 2018, according to the World Health Organization. Several studies shown that transferrin is a potential cancer biomarker because tumour cells are able to overexpress high levels of transferrin compared with their normal counterparts. In this context, this paper describes the development of an electrochemical immunosensor for the detection of transferrin (Tf), in the forms apo-Tf (non-iron-bound) and holo-Tf (iron-bound). The immunosensor was based on the immobilization of the polyclonal antibody anti-transferrin (anti-Tf) by the method of covalent crosslinking, employing the zero-length agents 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and n- hydroxysuccinimide (NHS). As transducing surface, ITO (índium-tin oxide) slides have been used and the results were obtained by the adequacy of the experimental data to Randles equivalent circuit. All measures were performed by the electrochemical impedance spectroscopy (EIS) technique, in 4 mmol L-1 potassium hexacyanoferrate (II) prepared in phosphate buffer pH 7.4. The immunosensors characterization was performed using the technique of EIS and cyclic voltammetry (CV), evaluating the electrochemical response of apo-Tf and holo-Tf. It was observed that the devices developed were capable of detecting both forms of Tf, in terms of charge transfer resistance (Rct). The best experimental conditions were evaluated for the development of the immunosensors, performing studies about the measure of the geometrical area of ITO, the activation of the eletrodic surface, the mean of the antibody immobilization, the anti-Tf incubation time and concentration and the antigens incubation time. Analytical curves have been built for each antigen, using five levels of concentration in duplicate. It was performed an initial study for the full validation of the developed devices. For this, it was estimated the figures of merit of limit of detection (LOD) and of quantification (LOQ), precision and linearity, the last being statistical by linear regression and lack of fit test in the 95% level of confidence. Thus, the developed immunosensors were applied in the detection of two cancer cells A549 (lung cancer) and MCF-7 (breast cancer), comparing with the healthy kidney lineage cell BHK. Intending to evaluate if the obtained responses differ significantly from the control cells (BHK), it was performed an one-factor variance analys (ANOVA) and a Dunnett’s test in 95% confidence level. This way, it was observed that the impedimetric response of healthy cells differ significantly from the cancerous cells, indicates the immunosensors potential for cancer diagnosis. Thereby, the device constructed can be consider as an advance for the detection of apo-Tf and holo-Tf, as well as in fast and low cost clinical diagnosis.